A Comparative Analysis of Fiscal Policy Changes in Selected European Union Countries outside the Eurozone - Szymańska, Agata (Comparative Economic Research. Central and Eastern Europe, 2019)
The aim of this article is to investigate the fiscal policy changes in six Central and Eastern European countries outside the Eurozone: Bulgaria, the Czech Republic, Croatia, Hungary, Poland and Romania. The analysis covers the period from 2004 to 2017. The study uses changes in the cyclically‑adjusted primary balance as a main indicator to assess the fiscal policy stance. The results indicate that, in general, over the period from 2004 to 2017, the fiscal stance in these countries was somewhat contractionary.